2008
DOI: 10.1128/jvi.02354-07
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of Multiple Poliovirus Molecular Clocks Covering an Extended Evolutionary Range

Abstract: We have calibrated five different molecular clocks for circulating poliovirus based upon the rates of fixation of total substitutions (K t ), synonymous substitutions (K s ), synonymous transitions (A s ), synonymous transversions (B s ), and nonsynonymous substitutions (K a ) into the P1/capsid region (2,643 nucleotides). Rates were determined over a 10-year period by analysis of sequences of 31 wild poliovirus type 1 isolates representing a well-defined phylogeny derived from a common imported ancestor. Simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
171
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(190 citation statements)
references
References 89 publications
(106 reference statements)
16
171
1
2
Order By: Relevance
“…These higher rates are evinced despite a wide range of mean rates; there was more variability among mean rates of enterovirus evolution than among those of isolates from five other genera (the standard deviation for enterovirus rates was four times [VP1] and two times [3D pol ] greater than for the other genera). Our novel and collected VP1 rates are similar to published rates of the entire P1 structural region (15,29,30), and our 3D pol rates echo that of an adjacent nonstructural region of a veterinary enterovirus (29). The striking similarity between evolutionary rates of structural and nonstructural picornavirus genes has not previously been discussed in the literature, but for each virus the rates were remarkably consistent with the estimated rates for both regions.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…These higher rates are evinced despite a wide range of mean rates; there was more variability among mean rates of enterovirus evolution than among those of isolates from five other genera (the standard deviation for enterovirus rates was four times [VP1] and two times [3D pol ] greater than for the other genera). Our novel and collected VP1 rates are similar to published rates of the entire P1 structural region (15,29,30), and our 3D pol rates echo that of an adjacent nonstructural region of a veterinary enterovirus (29). The striking similarity between evolutionary rates of structural and nonstructural picornavirus genes has not previously been discussed in the literature, but for each virus the rates were remarkably consistent with the estimated rates for both regions.…”
supporting
confidence: 75%
“…The genus Enterovirus is also by far the largest and most diverse genus in the family (2), which has allowed for more rate analyses of enteroviruses than of other genera. While all enterovirus substitution rates are of serotypes and most other available substitution rates are of species, the substitution rates of an enterovirus species should closely resemble the average of its serotype rates (30). However, our analyses showed that slower-evolving nonenterovirus species have much longer TMRCAs, which means they have had more time to become saturated at synonymous positions.…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…To improve the interpretation of the data in Fig. 3F, we added Table S3, which depicts the amount of synonymous changes from PV1(M) as a percentage of total nucleotides in the coding domain P1, P2, and P3 (36). Whereas the number of natural synonymous changes in the PVs and CAV20 is large, the changes acquired in P(1+2+3) Max In PV-infected cells, icosahedral "procapsids" (also known as "empty capsids") (35,44) are formed that, remarkably, are void of viral or cellular RNAs.…”
Section: Resultsmentioning
confidence: 99%
“…The date of the initiating OPV dose for the AFP case patient described in this study was estimated from the K s (synonymous substitutions per synonymous site) and K t (total substitutions per site) values by assuming evolution rates of 0.032 synonymous substitutions per synonymous site per year and 0.011 total substitutions per site per year (Jorba et al, 2008).…”
Section: Methodsmentioning
confidence: 99%